Physical performance in highest-level soccer: Comparison between FIFA World Cup and UEFA Champions League matches - Modric, T.; Sattler, T.; Morgans, R.; Pavlinovic, V.; Mandic, A. (SportMont, 2023)
Match running performance (RP) of Union of European Football Associations Champions League (UCL) and Fédération Internationale De Football Association World Cup (WC) players are often investigated separately; however, no study to simultaneously observed RP in both competitions. Therefore, the main objective of this study was to provide a comparative analysis of RP of professional soccer match-play across two highest-level soccer competitions: UCL and WC. The RPs (UCL; n=244, WC; n=581) of professional soccer players were analyzed using optical systems, and classified according to their playing positions as: central defenders (CD), fullbacks (FB), central midfielders (CM), wide midfielders (WM) and forward (FW). The RP variables included total distance and high intensity running (>5.5 m/s). One-way analysis of variance was used to examine position-specific differences between RP in WC and UCL, while Cohen`s d was used to identify effect sizes. Results indicated that CDs, FBs, CMs, and WMs from UCL covered significantly greater total distance than their counterparts from WC (all moderate effect sizes). In addition, CDs from UCL achieved greater amount of high intensity running than CDs from WC (small effect size). This study demonstrated differences in various aspects of physical performance between two highest-level soccer competitions with variations dependent upon playing position. The findings enabled a more thorough understanding of the physical requirements for playing in UCL and WC, and may have direct consequences for specific training programs.